Indications for destructive ocular surgeries in Nigeria - Monsudi, KF; Ayanniyi, AA; Balarabe, AH (Nepalese Journal of Ophthalmology, 2013)
Introduction: Destructive ocular surgery (DOS) means eye loss. An audit of its indications would be useful in reducing its incidence. Objective: To determine indications for destructive ocular surgeries. Materials and methods: The case records (files) of all the patients who had DOS in a tertiary health facility in Nigeria from January 2004 to December 2011 were reviewed retrospectively. The information extracted include the bio data, indication for DOS, type of surgery performed and history of the use of traditional eye medications (TEM) and willingness to use an artificial eye (AE). Results: Thirty-seven patients had DOS. The mean age of the patients was 35.51years (SD 21.6) and the male to female ratio was 2.1:1. Evisceration was the commonest DOS performed , in 30 eyes (81.1 %). The most common indication for DOS was intraocular infection, in 15 eyes (40.5 %), followed, among others, by trauma in 13 (35.1 %) and malignant ocular tumours in 4 (10.8 %). There was association between age and indication for DOS (P = 0.032). Many patients, 15 (40.5%), used TEM and most, 34 (91.9%), refused an artificial eye (AE) after surgery. Conclusions: The most common indication for DOS in this study was intraocular infection. Evisceration was the commonest destructive eye surgery offered. Nepal J Ophthalmol 2013; 5(9):24-27 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7817